Using the "Plotagon Story" Application to Improve Listening Skills at STAI At-Tanwir Bojonegoro - Afifah, Anis (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Teaching the Arabic language in the twenty-first century is diverse, because there are methods learned to develop educational materials in teaching the Arabic language. When I saw the researcher at the Islamic University of Tanweer, she found information that the students’ results were not excellent in the Arabic language skills, especially in teaching the listening skill, because the skill Listening is one of the standards in teaching the Arabic language. The reason for this is because the teacher only uses anecdotal anecdote without benefiting from the development of existing digital educational methods. Students feel bored and exhausted in learning the Arabic language, especially in the listening skill. The researcher developed and applied the digital learning tool “Plotagon Story” to improve the listening skill. This research is conducted using a quantitative approach. The objectives of this research are: 1) To find out the application of the digital educational method “Plotagon Story” to improve the listening skill at the level of university students, 2) To know the effectiveness of the digital educational method “Plotagon Story” to improve the listening skill at the level of university students. The digital educational method that the researcher used has an effectiveness in the ability of students, due to the standard of results obtained by the experimental group and the control group in the pre test and the post test. The score in the pre test is 67.75, and in the post test it is 89.5. There is effectiveness in applying the method. Digital educational "Plotagon Story".